Evading brittle fracture in submicron-sized high entropy intermetallics in dual-phase eutectic microstructure. (October 2020) - Ding, Z.Y.; He, Q.F.; Chung, D.; Yang, Y.
Abstract: Conventional Laves phase is extremely brittle at room temperature. However, through a systematic study, we showed that the quinary Co-Cr-Fe-Ni-Nb Laves phase in a eutectic high entropy alloy (EHEA) can be plastically deformed at room temperature when its size is refined below 200 nm. Based on our current results, we propose a general micromechanical model that not only explains the suppression of cracks in the high entropy Laves phase but also enables the extraction of its fracture toughness even when the high entropy Laves phase deforms and cracks in a dual-phase microstructure. Graphical abstract: Image, graphical abstract